Effect of strain rate and saturation on uniaxial dynamic compressive behaviours of mortar. Issue Volume 17:Issued 9(2016) (20th October 2016) - Tian, Zhenghong; Bu, Jingwu; Bian, Ce; Peng, Zhihai
Abstract : The effect of moisture content on the compressive mechanical behaviours of cement mortar under different high strain rates is studied in this paper. The rapid impact testing, i.e. the strain rates of 80, 100, 150, 200 and 250 s − 1 by Split Hopkinson pressure bar, on number of specimens with special water/cement ratio of 0.50 and saturations as 0%, 25%, 50%, 75% and 100%, respectively, was executed. The dynamic compressive behaviours were analysed in terms of the maximum stresses, elastic modulus, critical strain at maximum stresses and ultimate strains at failure. Results indicated that similarity existed in the shape of strain–stress curves of mortars with different moisture subjected to different strain rates of impact loading, i.e. the upward section presented bilinear characteristics, while the descending stage was almost linear. As strain rate increases, the dynamic compressive strength, elastic modulus and critical strain at maximum stress increase which can be ascribed to the dynamic fracture effect and the microscope inertia effect. Besides, it was shown that desiccation provokes an increase in mortar strength and deformation behaviour of the studied mortar with different saturation caused by capillary depression and microcracking. Drying effect has to be considered in modelling of the coupling between desiccation and mechanical behaviour of the mortar. Finally, the multi-parametric statistical analysis of water content and strain rate on the mechanical behaviours of cement mortar subjected to dynamic loading is detailed.